Pengembangan Profesionalisme Guru Solusi Tantangan Era Society 5.0 - Windi Windi; Feni Indriyani (Pendekar : Jurnal Pendidikan Berkarakter, 2023)
Science continues to develop according to the times, therefore teachers are required to be able to keep up with the times. Currently, it is the era of the industrial revolution 5.0, where in this era there has been significant change. In this era, technology is freely accessible to all groups. Society 5.0 is an era where all advanced technology becomes an important aspect of human life. The Society 5.0 era is an era where society is centered on balancing economic progress with a system that unites cyberspace and physical space in solving social problems. In the era of industrial revolution 5.0, technological developments in education are a challenge in itself as a teacher. In the Society 5.0 era, there are many changes in education which are a challenge for teachers. Teachers need to develop their potential in digital skills and creative thinking. To overcome these challenges, teachers need professional development in accordance with current developments. This professional development includes joining teacher organizations, taking part in training and continuing education as well as teaching evaluations and writing scientific papers.